Design of highly active Ni catalysts supported on carbon nanofibers for the hydrolytic hydrogenation of cellobiose - Frecha, Esther; Remón, Javier; Torres, Daniel; Suelves, Isabel; Pinilla, José Luis (Frontiers in Chemistry, 2022)
The direct transformation of cellulose into sugar alcohols (one-pot conversion) over supported nickel catalysts represents an attractive chemical route for biomass valorization, allowing the use of subcritical water in the hydrolysis step. The effectiveness of this process is substantially conditioned by the catalyst hydrogenation ability, determined by design parameters such as active phase loading and particle size. Herein, mechanistic insights into catalyst design for superior activity were outlined using the hydrolytic hydrogenation of cellobiose as a model reaction. Variations in the impregnation technique (precipitation in basic media, incipient wetness impregnation or the use of colloidal-deposition approaches) endowed carbon nanofibers (CNF) supported catalysts within a wide range of Ni crystal sizes (5.8-20.4 nm) and loadings (5-14 wt. %). The link between the properties of these catalysts and their reactivity has been established using characterization techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma-optical emission spectroscopy (ICP-OES). A fair compromise between the Ni surface area (3.89 m2/g) and its resistance against oxidation was found for intermediate crystallite sizes (~11.3 nm) loaded at 10.7 wt. %, affording the hydrogenation of 81.2 % of cellobiose to sorbitol after 3 h of reaction at 190 ºC and 4.0 MPa H2 (measured at room temperature). The ease of oxidation of Ni at smaller particle sizes hampered the use of highly dispersed catalysts to reduce the metal content requirements.